Dose-Dependent Induction of an Idiotypic Cascade by Anti-Glycosaminoglycan Monoclonal Antibody in apoE−/− Mice: Association with Atheroprotection - Sarduy, Roger; Brito, Victor; Castillo, Adriana; Soto, Yosdel; Griñán, Tania; Marleau, Sylvie; Vázquez, Ana María (Frontiers in Immunology, 2017)
Atherosclerosis, the underlying pathology of most cardiovascular diseases, is triggered by the retention of apolipoprotein B (apoB)-containing lipoproteins in the arterial wall, through electrostatic interactions with glycosaminoglycan (GAG) side chains of proteoglycans. Previously, we reported the antiatherogenic properties of the chimeric monoclonal antibody (mAb) chP3R99-LALA, which binds sulfated GAGs, inhibits low density lipoprotein (LDL)-chondroitin sulfate (CS) association and abrogates LDL oxidation and foam cell formation. In preventive and therapeutic settings, apoE-deficient (apoE-/-) mice immunized with 50 µg of this mAb showed reduced atherosclerotic lesions, related with the induction of autologous anti-GAG antibodies. Knowing that age and sex are major non-modifiable risk factors in the development of atherosclerosis, the present study aimed to assess the influence of these variables on the capacity of chP3R99-LALA mAb to generate an anti-CS antibody response. Also, we aimed at defining the impact of the dose of chP3R99-LALA on the anti-CS antibody induction and the atheroprotective effect of this mAb in apoE-/- mice. Neither age nor sex had an impact in the IgG anti-chondroitin sulfate (CS) antibody response induced by s.c. immunization with this mAb. Moreover, chP3R99-LALA mAb reduced atherosclerotic lesions to a similar extent in both young male and female apoE-/- mice fed a hypercholesterolemic diet and in middle-aged female apoE-/- mice with spontaneous lesions. On the other hand, increasing the dose of chP3R99-LALA (200 µg vs 50 µg) elicited an anti-idiotype antibody cascade characterized by higher levels of anti-idiotype (Ab2), anti-anti-idiotype (Ab3) and anti-CS antibody responses. Moreover, this dose increment resulted in a striking reduction of aortic atherosclerotic lesions in immunized mice.